Child-Parent agreement on quality of life of overweight children: Discrepancies between raters - Xavier CC Fung (Wolters Kluwer Medknow Publications, 2018)
Introduction: Kid-KINDL, a health-related quality of life (HRQoL) instrument for children, contains paralleled child-reported and parent-proxy versions. However, parents may rate HRQoL differently from children do; thus, health-care providers may be misled by the parent-rated HRQoL to assess the health of children. Thus, understanding the agreement between parent- and child-rated HRQoL is important. This study aimed to investigate the agreement between child- and parent-rated Kid-KINDL, including total score and domain (physical, emotional, self-esteem, friend, family, and school) scores. Methods: A total of 96 dyads of 8 to 12-year-old overweight children were recruited. Child-reported and parent-proxy Kid-KINDL were completed by children and parents (70.8% mother; 19.8% father), respectively. Statistical significance of child-parent discrepancies was analyzed using paired t-test and magnitude of discrepancies was analyzed using Cohen's d. Regression analyses were used to examine the potential predictors (age, gender, body mass index, family income, and raters) on score differences. Results: Significant differences were found in total score (d = −0.26) and three subscales (emotional, d = 0.21; self-esteem, d = −0.33; and school, d = −0.56) with small-to-medium magnitudes. Regression analyses revealed that father as rater significantly explained the score differences in total (standard coefficient β = −0.266, P = 0.013), emotional (β = −0.224,P = 0.038), and school (β = −0.215, P = 0.045). Conclusion: Parents seemed to be optimistic when rating on their overweight children's HRQoL. Health-care providers should be aware of this issue when using parent-reported Kid-KINDL and do not miss out any risk on children's HRQoL. Furthermore, the results may suggest health-care providers improving child-parent interaction. They can not only align parent with child, but also align with every caregiver.